New investigations at Kalambo Falls, Zambia: Luminescence chronology, site formation, and archaeological significance. Issue 85 (August 2015) - Duller, Geoff A.T.; Tooth, Stephen; Barham, Lawrence; Tsukamoto, Sumiko
Abstract: Fluvial deposits can provide excellent archives of early hominin activity but may be complex to interpret, especially without extensive geochronology. The Stone Age site of Kalambo Falls, northern Zambia, has yielded a rich artefact record from dominantly fluvial deposits, but its significance has been restricted by uncertainties over site formation processes and a limited chronology. Our new investigations in the centre of the Kalambo Basin have used luminescence to provide a chronology and have provided key insights into the geomorphological and sedimentological processes involved in site formation. Excavations reveal a complex assemblage of channel and floodplain deposits. Single grain quartz optically stimulated luminescence (OSL) measurements provide the most accurate age estimates for the youngest sediments, but in older deposits the OSL signal from some grains is saturated. A different luminescence signal from quartz, thermally transferred OSL (TT-OSL), can date these older deposits. OSL and TT-OSL results are combined to provide a chronology for the site. Ages indicate four phases of punctuated deposition by the dominantly laterally migrating and vertically aggrading Kalambo River (∼500–300 ka, ∼300–50 ka, ∼50–30 ka, ∼1.5–0.49 ka), followed by deep incision and renewed lateral migration at a lower topographic level. A conceptual model for site formation provides the basis for improved interpretation of the generation, preservation, and visibility of the Kalambo archaeological record. This model highlights the important role of intrinsic meander dynamics in site formation and does not necessarily require complex interpretations that invoke periodic blocking of the Kalambo River, as has previously been suggested. The oldest luminescence ages place the Mode 2/3 transition between ∼500 and 300 ka, consistent with other African and Asian sites where a similar transition can be found. The study approach adopted here can potentially be applied to other fluvial Stone Age sites throughout Africa and beyond.